An English E-learning Application Design Based On Android - Rinanda Ulfa Mardhotillah (Fakultas Ilmu Komputer, Unversitas Muhammadiyah Riau, 2019)
The development of communication technology in the field of education has an impact with the rise of virtual education or E-learning is a method of learning by using communication technology and Internet information. With the development of technology, the media books that have been used slowly began to switch to digital media. Digital media has several types of devices that can be used as a substitute media for books such as television, PC (Personal Computer), laptops and smartphones. Of the several digital devices that allow for easy to use and flexible is a smartphone. According to IDC (International Data Corporation), the smartphone market worldwide grew 1.1% from the third quarter of 2016, with 363.2 million shipments. Android dominates the smartphone market with 86.8% share. And Samsung, being the number one contributor remains in the top spot. The Directorate General of Primary and Secondary Education reports that the value of English subjects in the National Examination is low. The concrete picture of the result of the national survey of English language learning in 2009, the junior high student test scores low and very heterogeneous, the average value is 44.71 with a range of 0 - 95. From the explanation of the problem, it is necessary to realize a solution for someone interested even desire to learn English. One interesting solution to apply is Electronic Learning (E-learning). By using E-learning, will facilitate the user in learning something, this is because users can access the material through a smartphone. Users can learn and test capabilities through E-learning applications, wherever and whenever.